Carbon Aerogels With Kaolin Addition For Supercapacitors Application. Issue 1 (September 2020) - Xu, Yuelong; Ren, Bin; Wang, Shasha; Liu, Zhenfa
Abstract: Carbon aerogels with excellent electrochemical properties and 3D porous structure are prepared from the reaction of phloroglucinol (P), resorcinol (R) and formaldehyde (F) under ascorbic acid (VC) catalyzing with kaolin (KL) addition. Because of the double-layer capacitance behavior, CAs have been used as supercapacitors for energy storage. The reaction mechanism of the wet aerogels formation is analyzed. Meanwhile, the chemical environments of CAs surface is systematically investigated using X-ray photoelectron spectroscopy (XPS). The cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) measurements and electrochemical impedance spectroscopy (EIS) are adopted to studied the excellent electrochemical properties of different samples. The specific capacitance (SC) is up to 162 F g −1, and 97% of initial capacitance is retained over 1000 cycles at a current density of 1.0 A g −1 .